Field Evaluation of Certain Chemicals and Biopesticides against Pod Borer, Helicoverpa armigera (Hubner) in Chickpea: An Experimental Research - Mohite, Prajakta Anil; Khan, Shaik Ahmed Razack (Research Highlights in Agricultural Sciences Vol. 6, 2022)
The primary goal of this study was to learn about the effects of chemicals and biopesticides on H.armigera control. An experiment was carried out at the research plot of the Department of Agricultural Entomology at Central Research Farm, Sam Higginbottom University of Agriculture, Technology and Sciences, Prayagraj during the rabi season of 2021. With seven treatments and one controls plot, the field was laid out in a randomised block design (RBD). The mean larval population plant was measured the day before, three, seven, and fourteen days after each spray. When compared to the control, all of the pesticides tested significantly reduced pest infestation. Based on pest population, grain yield, and B: C ratio, the following results were obtained: T4 Spinosad 45% SC is the most effective treatment against gram pod borer of Mean larvae population producing maximum yield and recording greatest Cost-Benefit ratio compared to other treatments. When the cost-benefit ratio was calculated, an interesting result was obtained. The best and most cost-effective treatment among those tested was Spinosad 45% SC (1:3.98), Spinetoram 11.7 SC (1:3.95), followed by Chlorantraniliprole 18.5% SC (1:3.82), Flubendamide 39.35% SC (1:3.73), Bacillus thuringiensis 1x108 CFU/ml (1:3.21), and Beauveria bassiana 1x108 CFU/ml (1:2.96), The lowest cost benefit ratio was recorded in Metarhizium anisopilae 1x108 CFU/ml (1:2.80) when compared to Control (1:1.95).